If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -1)(2x + -3) = 0 Reorder the terms: (-1 + 8x)(2x + -3) = 0 Reorder the terms: (-1 + 8x)(-3 + 2x) = 0 Multiply (-1 + 8x) * (-3 + 2x) (-1(-3 + 2x) + 8x * (-3 + 2x)) = 0 ((-3 * -1 + 2x * -1) + 8x * (-3 + 2x)) = 0 ((3 + -2x) + 8x * (-3 + 2x)) = 0 (3 + -2x + (-3 * 8x + 2x * 8x)) = 0 (3 + -2x + (-24x + 16x2)) = 0 Combine like terms: -2x + -24x = -26x (3 + -26x + 16x2) = 0 Solving 3 + -26x + 16x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -8x)(3 + -2x) = 0Subproblem 1
Set the factor '(1 + -8x)' equal to zero and attempt to solve: Simplifying 1 + -8x = 0 Solving 1 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = 0 + -1 -8x = 0 + -1 Combine like terms: 0 + -1 = -1 -8x = -1 Divide each side by '-8'. x = 0.125 Simplifying x = 0.125Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {0.125, 1.5}
| m^2+30=-17m | | 14a+6a^2= | | y-50=-5.67(x-10) | | 6x-4=9x-3 | | 2x^2+2x+13=8x^2-4x+1 | | (-9)=2/3x-17 | | 8x+1=1x+6 | | x^4+3x-78=0 | | 3(4c+1)=2c+13 | | 3s(-2s)= | | x+1=6x-x^2 | | 12+6x=8x | | 3sx-2s= | | 3=8r+1+2 | | (x^2+8x+17)/(x+2) | | -6w-3=21 | | 20x-21=2x+14 | | 3(4c+1)2c=13 | | 4*8cs+3c=8c | | 14b+5=10b+21 | | 7x+11=-24 | | 5*12/n-3d=12 | | -25d-3.2=74.1 | | -2x+7(1-(-3x))=-19+3x | | 2(10-2b)+b=6 | | 7x+6=6x-2 | | 7x-5x-3=6 | | (-4)+(-6)(+4)-(-1)= | | 3k*t-k=3k | | 3*7+4h=7 | | -2x^2+4=x^2+x-7 | | 2a+a-5=5 |